2007
DOI: 10.1002/uog.5171
|View full text |Cite
|
Sign up to set email alerts
|

Delta‐NT and center‐specific ultrasound nuchal translucency medians

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The second type of quality assurance is quantitative. Individual operator's specific NT distributions adjusted for CRL can be produced and compared against an accepted reference distribution …”
Section: Introductionmentioning
confidence: 99%
“…The second type of quality assurance is quantitative. Individual operator's specific NT distributions adjusted for CRL can be produced and compared against an accepted reference distribution …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, calculation of multiples of the median (MoM) values provides a useful parameter that can be used to assess variation between operators. The median NT‐MoM value should be 1.0 if the NT measurements of a single operator or group of operators do not deviate from the modeled median reference curve13–16. To ensure good quality NT measurements, the accepted median NT‐MoM of an operator should be limited, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the LC software this is done by calculating the NT-MoM, while in Astraia the Δ-NT is used. However, it has been shown that the method of calculating a LR for the NT measurement has no large infl uence on the risk calculation [5,8] .…”
Section: Resultsmentioning
confidence: 99%